Tequila! : distilling the spirit of Mexico - Gaytán, Marie Sarita, 1974- (Stanford University Press, 2014)
Italy has grappa, Russia has vodka, Jamaica has rum. Around the world, certain drinks-especially those of the intoxicating kind-are synonymous with their peoples and cultures. For Mexico, this drink is tequila. For many, tequila can conjure up scenes of body shots on Cancún bars and coolly garnished margaritas on sandy beaches. Its power is equally strong within Mexico, though there the drink is more often sipped rather than shot, enjoyed casually among friends, and used to commemorate occasions from the everyday to the sacred. Despite these competing images, tequila is universally regarded as.